2008
DOI: 10.1021/jm800567v
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Siderophore Biosynthesis in Mycobacterium tuberculosis with Nucleoside Bisubstrate Analogues: Structure−Activity Relationships of the Nucleobase Domain of 5′-O-[N-(Salicyl)sulfamoyl]adenosine

Abstract: 5′-O-[N-(salicyl)sulfamoyl]adenosine (Sal-AMS) is a prototype for a new class of antitubercular agents that inhibit the aryl acid adenylating enzyme (AAAE) known as MbtA involved in biosynthesis of the mycobactins. Herein, we report the structure-based design, synthesis, biochemical, and biological evaluation of a comprehensive and systematic series of analogues, exploring the structureactivity relationship of the purine nucleobase domain of Sal-AMS. Significantly, 2-phenyl-Sal-AMS derivative 26 exhibited exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 100 publications
6
162
2
Order By: Relevance
“…The use of salicyl-AMP analogs initially developed by Quadri and Tan (10) and extended by others (28,40) as inhibitors of M. tuberculosis growth provides a template for targeting the A domains of the MBT megasynthase for drug development. The focus on salicyl-AMP analogs to inhibit the function of MbtA was viable because these analogs were unlikely to inhibit host metabolic processes.…”
mentioning
confidence: 99%
“…The use of salicyl-AMP analogs initially developed by Quadri and Tan (10) and extended by others (28,40) as inhibitors of M. tuberculosis growth provides a template for targeting the A domains of the MBT megasynthase for drug development. The focus on salicyl-AMP analogs to inhibit the function of MbtA was viable because these analogs were unlikely to inhibit host metabolic processes.…”
mentioning
confidence: 99%
“…Many pathogens, for example, have multiple iron uptake pathways; if one is inhibited, another may or may not compensate. However, recent work demonstrated that Mycobacterium tuberculosis cultures are susceptible to picomolar levels of chemical inhibitors of MbtA, an enzyme catalyzing biosynthesis of the aryl cap of mycobactin siderophores (23)(24)(25). Like Aspergillus sp., mycobacteria have been predicted to depend on variants of the same siderophore for multiple steps in the uptake, internalization, and storage of iron and hence may be especially susceptible to chemical inhibition of mycobactin biosynthesis.…”
mentioning
confidence: 99%
“…Several attempts were made to identify compounds that prevent siderophore synthesis and transport. A salicylsulfamoyl adenosine and other nucleoside bisubstrate analogous were found to prevent the early step of siderophore synthesis of Yersinia and Mycobacterium (Ferreras et al 2005;Miethke and Marahiel 2007;Neres et al 2008).…”
Section: Depletion Of Ironmentioning
confidence: 99%